Soft systems modelling of food waste management in a circular economy Framework - Lantin, Jahziel P. (Animo Repository, 2023)
Food waste management was explored because of the increase in food waste generations and its environmental impact. Other developing countries have already implemented policies on food waste reduction and treatment, but no study has been made in the Philippines yet. This study aimed to assess the current situation of food waste in the Philippines and developed a model on a food waste management system in the context of a circular economy. System Dynamics was used for model development and for the analysis of HB 3370 when implemented. Analytical Hierarchy Process (AHP) was used to determine the most preferred option among the scenarios given. The multi-sectoral implementation was the scenario that has the highest reduction of 20% in food waste generation and had 6.34% of the generated food waste treated based on System Dynamics Simulation. This scenario was the most preferred by experts during the AHP having a final weight of 0.3386.